(z+9)(3z+4)=0

Simple and best practice solution for (z+9)(3z+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (z+9)(3z+4)=0 equation:


Simplifying
(z + 9)(3z + 4) = 0

Reorder the terms:
(9 + z)(3z + 4) = 0

Reorder the terms:
(9 + z)(4 + 3z) = 0

Multiply (9 + z) * (4 + 3z)
(9(4 + 3z) + z(4 + 3z)) = 0
((4 * 9 + 3z * 9) + z(4 + 3z)) = 0
((36 + 27z) + z(4 + 3z)) = 0
(36 + 27z + (4 * z + 3z * z)) = 0
(36 + 27z + (4z + 3z2)) = 0

Combine like terms: 27z + 4z = 31z
(36 + 31z + 3z2) = 0

Solving
36 + 31z + 3z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(9 + z)(4 + 3z) = 0

Subproblem 1

Set the factor '(9 + z)' equal to zero and attempt to solve: Simplifying 9 + z = 0 Solving 9 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + z = 0 + -9 Combine like terms: 9 + -9 = 0 0 + z = 0 + -9 z = 0 + -9 Combine like terms: 0 + -9 = -9 z = -9 Simplifying z = -9

Subproblem 2

Set the factor '(4 + 3z)' equal to zero and attempt to solve: Simplifying 4 + 3z = 0 Solving 4 + 3z = 0 Move all terms containing z to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3z = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3z = 0 + -4 3z = 0 + -4 Combine like terms: 0 + -4 = -4 3z = -4 Divide each side by '3'. z = -1.333333333 Simplifying z = -1.333333333

Solution

z = {-9, -1.333333333}

See similar equations:

| 2b+7=4b+2 | | 15+4x=6+7x | | -2(-b-4)=-(b-8) | | 8.7x+4.42=-11.3x+3.18 | | 6+4w=13+3w | | -8(x+7)+5=-51 | | 4r+6=13+2r | | x*2+4*x+y*2-21=0 | | ln(4x^6+2x^3)=y | | 180=120x | | -2(b-4)=-(b-8) | | x^2+1-11=0 | | 4xn+2=10+2n | | 20w^2+10w+40=0 | | 16x^2-96x+4y^2+8y=-84 | | 96j+245=53 | | log(2)18=x | | 12x+9-5x^2=0 | | -8x+9x=-2 | | 5n+1=2n+3 | | 6.7x-3.4=16.7 | | 5x-9+4x=3x+30 | | 7p-23=-17+8p | | 2v+7=5v+4 | | 45=360+x | | 2r-16=-6+4r | | 4g+20=10g+5 | | Y=8sec(5x) | | 2(x-7)-9=-23 | | 5(3x+2)=7 | | 3n+2=1n+12 | | (x+10)(x+5)+(x+-3)(x+12)+(x+11)(x+30)=106 |

Equations solver categories